Correlation of COVID-19 antigen test and CBNAAT results at a single tertiary care hospital in North India: an experience - Gupta, Surbhi; Shukla, Anju; Singh, Poonam; Siddiqui, Areena H. (International Journal Of Community Medicine And Public Health, 2021)
Background: Nucleic acid amplification test (NAAT) is considered gold standard in the molecular diagnosis of CoV-2 infection but since it is costly, labor intensive and needs technical expertise, rapid chromatographic immunoassay for the qualitative detection of specific antigens to SARS CoV-2 have been devised. Objectives of this study was to compare the results of Antigen test and NAAT for CoV-2 infection carried out during the months of July and August 2020 by single tertiary care hospital in Lucknow, Uttar Pradesh and to determine the utility of rapid antigen test in the SARS CoV-2 diagnosis. Methods: All the patients who came to our hospital seeking admission during July 2020 and August 2020 were included in the study. A total of 1000 patients were included in this study. Results: Out of a total 1000 cases which were included in the study, 769 cases (76.9%) were found to be SARS CoV-2 negative by both antigen and CBNAAT, 100 cases (10.0%) were SARS CoV-2 positive by both antigen and CBNAAT tests. But in 131 cases (13.1%), antigen was not able to pick up the disease. It was also found that the Cycle Threshold (Ct) value for the discordant group was higher (Mean E= 28, Mean N2=33) when compared to the group where antigen was positive. Conclusions: The present study establishes the role of rapid antigen tests in contributing to the quick, point of care diagnosis of SARS CoV-2. These assays are safe, simple, and fast and can be used in local clinics and hospitals. These tests are very important for real-time patient management and infection control decision.